2021
DOI: 10.3389/fpsyg.2020.633265
|View full text |Cite
|
Sign up to set email alerts
|

Adaptability Promotes Student Engagement Under COVID-19: The Multiple Mediating Effects of Academic Emotion

Abstract: In response to the COVID-19 pandemic, millions of students in China followed an emergency policy called “Suspending Classes without Stopping Learning” to continue their study online as schools across the country were closed. The present study examines how students adapted to learning online in these unprecedented circumstances. We aimed to explore the relationship between adaptability, academic emotion, and student engagement during COVID-19. 1,119 university students from 20 provinces participated in this lon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
96
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 91 publications
(104 citation statements)
references
References 46 publications
5
96
0
3
Order By: Relevance
“…During the pandemic, university students showed a high level of interest in receiving psychological knowledge and interventions, especially for information that could help them alleviate negative psychological effects (Wang Z. et al, 2020 ). As adaptability has been identified as a key factor in protecting students from anxiety and depression during the Covid-19 pandemic (Zhang et al, 2021 ), fostering psychological flexibility could be a beneficial approach to addressing the negative consequences of pandemic on mental health (Kashdan and Rottenberg, 2010 ). Psychological flexibility is defined as the capacity to adapt one's behavior in a manner that incorporates conscious and open contact with thoughts and feelings (Scott et al, 2014 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…During the pandemic, university students showed a high level of interest in receiving psychological knowledge and interventions, especially for information that could help them alleviate negative psychological effects (Wang Z. et al, 2020 ). As adaptability has been identified as a key factor in protecting students from anxiety and depression during the Covid-19 pandemic (Zhang et al, 2021 ), fostering psychological flexibility could be a beneficial approach to addressing the negative consequences of pandemic on mental health (Kashdan and Rottenberg, 2010 ). Psychological flexibility is defined as the capacity to adapt one's behavior in a manner that incorporates conscious and open contact with thoughts and feelings (Scott et al, 2014 ).…”
Section: Discussionmentioning
confidence: 99%
“…Researchers around the world have called for researchers to examine the impact of the pandemic and school closures on students' anxiety, depression, and other outcomes (Holmes et al, 2020 ). Research suggests that the combined psychological pressure caused by the pandemic and the quarantine heightened anxiety and depression, particularly among university students (e.g., Brooks et al, 2020 ; Peng et al, 2020 ; Zhang et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…In a multi-national survey of undergraduate students, Nguyen et al (2021) reported that the majority preferred synchronous classes, which mode-especially when it involved active-learning techniques-correlated with higher levels of engagement and motivation. Student engagement and adaptability were also found to significantly correlate with academic emotion (Zhang et al, 2021). An analysis carried out at a university in Russia (Dikaya et al, 2021) revealed an association between students' attitudes to forced remote learning and their interpersonal communicative skills and thinking and learning styles.…”
Section: Literature Reviewmentioning
confidence: 98%
“…The Ministry of Education and Higher Education Qatar responded with robust emergency measures such as closing schools and using online platforms to virtually aid learning. Thus, ~30 million university students worldwide encountered a novel move from face to face traditional learning to virtual learning ( Wang and Zhao, 2020 ; Zhang et al, 2021 ). The pandemic has brought not only the risk of death from viral infection but also public mental health problems, such as anxiety and depression symptoms worldwide ( Wu et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Although the severe effect of the pandemic on students’ psychological well-being has been highlighted in previous studies, most of these are cross-sectional ( Lau et al, 2005 ; Chen et al, 2020 ; Wu et al, 2020 ). To date, few longitudinal studies have explored decreased PA, SL, and symptoms of anxiety among university students during the COVID-19 pandemic ( Wang and Zhao, 2020 ; Zhang et al, 2021 ). Documented changes in anxiety are divergent.…”
Section: Introductionmentioning
confidence: 99%